Comportamento do carbono orgânico em área úmida do cerrado (Vereda do Córrego Beija-Flor, Uberlândia/MG) - Machado, Henrique Amorim (2014)
Wetlands have become a focus of international attention since 1971, with the first global conference dedicated exclusively to this topic. Since then, it has consolidated as an important area of research, thanks to its transdisciplinarity and complexity, which allows a contribution of various branches of modern science. The pedology in this context aims to understand the dynamic that contribute to the genesis and evolution of soils in these landscapes, seeking ways to rational use and methodologies to ensure minimal impact of anthropogenic use in the surrounding areas. The soil organic carbon is used as an important indicator of ecosystem sustainability, being very sensitive to short-term changes caused by changes in the middle, either natural or anthropogenic origin. The objective of this research was to identify the standard accumulation of organic carbon within the wetland, analyzing both vertically, with different depths of analysis, or horizontally, with the points distributed from the toposequence, relating them to the dynamics of groundwater and soil physical properties. The survey was conducted on the upper course plateau of Uberabinha River, located between the cities of Uberlândia and Uberaba. Minas Gerais, administrative region of Triângulo Mineiro and Alto Paranaíba. Brazil. The organic carbon was quantified from the combustion method, while the humic fractions were quantified by the differential solubility and titration method. Six points were distributed in topossequence, with four collection depths: 0-10; 10-20; 20-30; and 30-50 cm. Carbon percentage found in the study area ranged from 1.7% to 17.7%, preferably concentrating on points downstream and closer to the surface. As groundwater moves away from the surface and the oxidation condition of organic matter is taken up, the carbon content decreases. In humin fraction, organic carbon has shown a similar dynamics to the total organic carbon, concentrating more on the surface and decreasing according to the groundwater debasement; in the fraction of humic acid, the organic carbon percentage ranged from 0.4% to 2 7%, with a different dynamic observed in the total organic carbon, due to its solubility conditions; and in the fraction of fulvic acid, organic carbon ranged from 0.1% to 2.4%. Through research, it was evident the influence of humidity on the decomposition of organic matter, showing that any change in average levels of groundwater have a major impact on the dynamics and processes involving the mineralization of organic carbon in plateau wetlands.